DAMPAK PERUBAHAN IKLIM TERHADAP MIGRASI LINGKUNGAN DAN KEAMANAN MANUSIA DI BANGLADESH - Madyar Dewi, Untari Narulita; Haqqi, Halifa; Mercia Karina (Indonesian Association for International Relations, 2023)
The research explains the impact of climate change which resulted in environmental migration from Bangladesh to India. This study aims to analyze the impact of climate change on environmental migration from Bangladesh to India. The method used is a qualitative method with data collection through literature studies with the concept of human security by UNDP and the theory of environmental migration by Graeme Hugo. The results of this study indicate that the impact of climate change which is massively occurring in Bangladesh raises